Ethiopia Economic Update, November 2012 : Overcoming Inflation, Raising Competitiveness - Geiger, Michael (World Bank, Washington, DC, 2017)
Since 2004 (Ethiopian Fiscal Year (EFY) 1997), Ethiopia has experienced strong and generally broad-based real economic growth of around 10.6 percent on average between then and 2011. Growth over the last nine years was far beyond the growth rates recorded in aggregate terms for Sub-Saharan Africa (SSA), which on average only reached 5.2 percent, less than half of Ethiopia's average real gross domestic product (GDP) growth rate during that period. Inspired by the East Asian experiences for a comparison of selected indicators and policies of Ethiopia and China/Korea), growth was induced through a mix of factors including agricultural modernization, the development of new export sectors, strong global commodity demand, and government-led development investments. The initial double digits growth rates have now manifested slightly lower but remain at high single-digit levels. The economy is expected to stabilize at around seven to eight percent in 2012, largely owing to improved performance in the agriculture sector. GDP growth is likely to stay around that margin up until 2016 (EFY 2008) driven by rising foreign investment and exports (Economist Intelligence Unit 2012). High inflation persists, but is on a slightly decreasing trend. Economic growth brought with it positive trends in reducing poverty, in both urban and rural areas. Ethiopia follows a strategy of increasing exports to facilitate growth. This is appropriate given the currently limited size of its domestic market and it is consistent with the development experience of some of the recently successful countries, particularly in East Asia. Export of goods growth is to a good extent driven by volume growth across a variety of product groups, which indicates that this growth is a result of recent efforts to increase and diversify the export base. Overall export and import developments result in a significantly increased trade deficit by 43 percent, up from US$5.5 billion in 2010/11 to US$7.9 billion.